Recurrent fusions in PLAGL1 define a distinct subset of pediatric-type supratentorial neuroepithelial tumors - Sievers, Philipp; Henneken, Sophie C; Blume, Christina; Sill, Martin; Schrimpf, Daniel; Stichel, Damian; Okonechnikov, Konstantin; Reuss, David E; Benzel, Julia; Maaß, Kendra K; Kool, Marcel; Sturm, Dominik; et al. (Acta neuropathologica, 2021)
Ependymomas encompass a heterogeneous group of central nervous system (CNS) neoplasms that occur along the entire neuroaxis. In recent years, extensive (epi-)genomic profiling efforts have identified several molecular groups of ependymoma that are characterized by distinct molecular alterations and/or patterns. Based on unsupervised visualization of a large cohort of genome-wide DNA methylation data, we identified a highly distinct group of pediatric-type tumors (n = 40) forming a cluster separate from all established CNS tumor types, of which a high proportion were histopathologically diagnosed as ependymoma. RNA sequencing revealed recurrent fusions involving the pleomorphic adenoma gene-like 1 (PLAGL1) gene in 19 of 20 of the samples analyzed, with the most common fusion being EWSR1:PLAGL1 (n = 13). Five tumors showed a PLAGL1:FOXO1 fusion and one a PLAGL1:EP300 fusion. High transcript levels of PLAGL1 were noted in these tumors, with concurrent overexpression of the imprinted genes H19 and IGF2, which are regulated by PLAGL1. Histopathological review of cases with sufficient material (n = 16) demonstrated a broad morphological spectrum of tumors with predominant ependymoma-like features. Immunohistochemically, tumors were GFAP positive and OLIG2- and SOX10 negative. In 3/16 of the cases, a dot-like positivity for EMA was detected. All tumors in our series were located in the supratentorial compartment. Median age of the patients at the time of diagnosis was 6.2 years. Median progression-free survival was 35 months (for 11 patients with data available). In summary, our findings suggest the existence of a novel group of supratentorial neuroepithelial tumors that are characterized by recurrent PLAGL1 fusions and enriched for pediatric patients.
Keywords: Neuroepithelial tumor; Gene fusion; Supratentorial; Supratentorial Neoplasms; mužské pohlaví; Transcription Factors; onkogenní fúze; dítě; Cell Cycle Proteins; Ependymoma; Child; transkripční faktory; PLAGL1; proteiny buněčného cyklu; supratentoriální nádory; ženské pohlaví; nádorové supresorové proteiny; Oncogene Fusion; EWSR1; Humans; FOXO1; Tumor Suppressor Proteins; EP300; ependymom; Female; lidé; Male